Acceptance and Usage of Webcasting Among Users of Selected Cyber Cafés in Klang Valley, Malaysia - Tengku Mohd Azzman Shariffadeen, Tengku Siti Aisha (2007)
The Internet is the world’s largest interconnected network. With broadband Internet connection, the transfer of text, audio and video was made possible through the streaming technology. This resulted in the birth of webcasting technology in 1995. However, even though the technology has been available for more than ten years, there is a lack of information and research conducted on the technology, particularly on who are the early adopters, and what would be the most viable content for adoption. Hence, the aim of this study is to understand the usage of webcasting among users of webcasting. This study also aims for looking at the acceptance of webcasting from the perspective of the Technology Acceptance Model (TAM) and to analyze the relationship between perceived usefulness (PU) and perceived ease of use (PEOU) with the behavioral intention (BI) to use webcasting among non-users of the technology.This study used the survey design and structured questionnaire as a means to gather data. A total of 221 respondents from a total of 15 cyber cafés in selected areas of the Klang Valley participated in this study. The respondents were selected using purposive sampling. The data was analyzed using the Statistical Package for Social Sciences (SPSS version 12). The statistical analysis used in the study consisted of descriptive analysis, Pearson’s correlations and the multiple regression. The results revealed the profile of webcasting users as male, young, students, educated with at least a diploma qualification but having no working experience. The most frequently used webcasting technology among webcasting users is the Internet radio. Since the technology is fairly new, the level of knowledge and skills in using the technology was moderate. The Internet is the most preferable source in becoming more aware of the technology. There is also acceptance of the technology among non-users of webcasting; perceived ease of use and usefulness was found to have a significant relationship with behavioral intention. The study partly validated and strengthened the basic TAM theory; non-users had more intention to use the webcasting technology if the perceptions towards the technology were positive. Finally, the study also proved that even though the usage of webcasting is still relatively low, the future of webcasting as an alternative media proves to be encouraging due to the acceptance of webcasting among non-users of the technology.